Optimizing Preventive Maintenance Scheduling of Centrifugal Pumps Using FTA and FMEA Techniques - Yosep Salfaridus Nong Sandro; Rusindiyanto Rusindiyanto (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2025)
Centrifugal pumps are critical assets within the production system of PT XYZ. Failures in their subcomponents can cause significant operational disruptions. This study aims to optimize the preventive maintenance scheduling for centrifugal pumps by integrating Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA). The FMEA identified the highest Risk Priority Numbers (RPNs) for the ball bearing (252), mechanical seal (240), and impeller lock (240), which are associated with risks such as overheating, leakage, and wear. Based on these findings, a revised preventive maintenance schedule comprising 63 tasks was developed. Implementing this optimized schedule increased machine reliability from 76.98% to 95%, corresponding to an 18.02% improvement in effective operational availability through reduced downtime. These results underscore the importance of a structured, risk-based preventive maintenance strategy for ensuring production continuity. The study recommends increasing the maintenance frequency for critical components, selecting more durable materials, and implementing regular condition monitoring. The findings demonstrate that risk-based maintenance strategies can significantly enhance system reliability and industrial process efficiency.